The Importance Of The Role Of Professional Ethics In The Sustainability Of A University - Renny Maisyarah; Dito Aditia Darma Nst; Fahrum Nisa; Ismail; Nur Azizah; Silvi Dwi Utari; Abdul Habib Sitompul (International Journal of Management, Economic and Accounting, 2024)
Professional ethics is an important foundation in maintaining the sustainability and credibility of a university. As a higher education institution, the university has a moral and professional responsibility to ensure academic integrity, maintain relationships between the academic community, and meet the expectations of society. Without the implementation of strong professional ethics, universities risk losing the trust of stakeholders, both internally and externally. This research aims to explore the role of professional ethics in university sustainability. The main focus is on how ethical values are applied in academic, administrative, and strategic decision-making activities.